1993
DOI: 10.1021/ac00060a607
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Disorders

Abstract: The clinical laboratory has indeed been challenged to aid in the diagnosis, prognosis, and treatment of psychological disorders. One of the major stumbling blocks has been the categorization of the various syndromes and diseases, and although this has improved by using the DSM-IIIR, much work remains (H1-H4)-The inability to do more research on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Researchers [38] suggested automatized systems for the sample collection. Researchers [39] found that across various fields of practice, disabled people having mental health problems have advised staying away due to societal issues.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers [38] suggested automatized systems for the sample collection. Researchers [39] found that across various fields of practice, disabled people having mental health problems have advised staying away due to societal issues.…”
Section: Related Workmentioning
confidence: 99%
“…• For a doctor to do the correct decision, the system must be simple in nature. Before the system is installed, usability tests shall be performed [39].…”
Section: Points To Remember While Designing Proposed -Ddssmentioning
confidence: 99%
“…The method of assessing and measuring psychological conditions or the socio-cultural associations of individuals with probable psychological disorders may be described as a psychological evaluation. In particular, the diagnosis is used to identify if a person's symptoms fulfill all particular psychological disorder requirements [1].…”
Section: Psychologicalmentioning
confidence: 99%
“…In the decision-making mechanism relying on AI Nunes, Pinheiro and Pequeno [1] indicated that many smart techniques were integrated. However, the automation of this strategy is very important, particularly when a multi-criteria assessment is required.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation